Academic entrepreneurship and institutional change in historical perspective. Issue 3 (3rd July 2017) - Wadhwani, R. Daniel; Galvez-Behar, Gabriel; Mercelis, Joris; Guagnini, Anna
Abstract: This article provides a historical perspective on academic entrepreneurship and its role in institutional change, and serves as an introduction to a special issue devoted to the subject. Unlike approaches that define academic entrepreneurship narrowly as the commercialization of academic research, we argue that historical research and reasoning justify a broader conceptualization focused on the pursuit of future forms of value in academic knowledge production, application, and transmission. Understood in this way, academic entrepreneurship has long been a significant driver of institutional change, not only within the academic world but also in shaping the organization of markets and states. The article develops this argument in three major sections. First, it draws out themes implicit within the historiography of science and technology that highlight the role of entrepreneurship in reshaping academia and its relationship to society. Second, it establishes conceptual foundations for more explicitly examining the processes by which academic entrepreneurship acted as a driver of institutional change. Finally, it synthesizes the findings of the articles in the special issue pertaining to these entrepreneurial processes. The article concludes by arguing for the role of history in rethinking academic entrepreneurship in our own time, and by outlining directions for further research.